A teoria dos fatos jurídicos processuais no processo civil do Estado Democrático Constitucional brasileiro - Ávila, Raniel Fernandes de (2017)
The "procedural legal fact" is controversial subject, being a concept generally little wanted by proceduralists. A plausible reason for this prejudice is that the terminology "juridical fact" arose among private law scholars, a circumstance that limited the importation to the (public) branch of the procedural law, especially at a time (“processualística” phase) in which the didactic autonomy was sought of procedural law in relation to substantive law. Once this ideology has been overcome, the barriers that block the construction of a theory of "juridical procedural facts" are removed. In fact, a group of Brazilian jurists is taking on the responsibility of building such a theory. The problem is that the aforementioned theoretical elaboration, located in the meanderings of the procedural propaedeutics, is based on Pontes de Miranda's theory of the legal fact, designed for a reality prior to the 1988 Constitution, which precedes even the Civil Procedure Code of 1973 and that always was applied in private law. Thus, contradictions arise with the civil process of the Brazilian Constitutional Democratic State, in the current phase of “formalism-evaluative”, especially because the key part of the theory of procedural legal facts is the ponteano concept of "automatic and infallible incidence" of the norm, which conflict with the contemporary hermeneutic conceptions, which situate the juridical norm as a result of the interpretation and that put the jurisprudence like source of the Law. To further cause perplexity, the theory of procedural legal facts deals with categories that were classically, or poorly viewed by the doctrine of the process, or unknown to proceduralists, such as the case of “procedural contracting” and “procedural act-fact”. Faced with this, importing such species into civil proceedings can be seen as a taboo difficult to overcome. It will be seen, however, that these shocks are merely apparent, because there are elements in the theory of procedural legal facts that make that construction a possible instrument to be applied - especially, when some necessary adjustments are made - to the civil process of the State Brazilian Constitutional Democratic, including the new Code of Civil Procedure (of 2015).